MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MELALUI PERMAINAN JUMP BOX (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The aim in this study was to determine the learning outcome long jump squat style through play approach jump box on fourth grade students N Yamansari 01 2013/2014 academic year. This research is a classroom action research. This study consisted of two cycles. Each cycle consists of planning, action, observation and reflection. This research was conducted in the District 01 Elementary School Yamansari Lebaksiu Tegal with research subjects IV class with 40 students consisting of 21 male students and 19 female students. The research instrument used is the observation sheet student activity, teacher observation sheet activities and practice tests. Technique data analysis was done descriptively and through hitingan predetermined formula. The results showed that the learning outcomes long jump squat style by using a jump box game this looks positive impact on students' mastery learning outcomes that exceed a predetermined KKM is 75 has risen in the first cycle of learning completeness reached 72.50% with a mean value -rata 78, while in the second cycle learning completeness reached 92.50% with an average value of 81.67. It can be concluded that learning style long jump squat jump box game approach has a positive influence, which can improve learning outcomes, interest and motivation to learn.